2022
DOI: 10.1007/s13399-022-03309-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the biosynthesis of oxyprenylated coumarins in calli from Ferulago campestris elicited by ferulic acid

Abstract: Previous and recent literature acquisitions suggested that cultured calli are an efficient and meaningful model to investigate the extent and fate of prenylation of phenylpropanoid cores in plants belonging to the Rutaceae and Apiaceae families upon administration of putative biosynthetic precursors. To this concern, in the present manuscript, we investigated the effect of supplementation of ferulic acid and umbelliferone on the biosynthesis of their oxyprenylated counterparts in Ferulago campestris (Besser) G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…48,49 Systematic research found 1300 secondary metabolite chemotypes in plants, microbes, and fungi. 50 The roots of Ferulago campestris, 51 Murraya paniculata 52 leaves, Aegle marmelos 53 fruits, and tonka bean seeds contain derivatives of coumarins with several biological functions. Synthetic coumarin-based heterocyclic analogues such azoles, sulfonyl, furan, and pyrazole have promise anticancer, antitumor, and anti-proliferative properties.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 Systematic research found 1300 secondary metabolite chemotypes in plants, microbes, and fungi. 50 The roots of Ferulago campestris, 51 Murraya paniculata 52 leaves, Aegle marmelos 53 fruits, and tonka bean seeds contain derivatives of coumarins with several biological functions. Synthetic coumarin-based heterocyclic analogues such azoles, sulfonyl, furan, and pyrazole have promise anticancer, antitumor, and anti-proliferative properties.…”
Section: Introductionmentioning
confidence: 99%